Keterampilan Pemecahan Masalah Fisika Siswa dalam Konteks Kehidupan Sehari-hari: Antara Pengakuan dan Fakta - Indah Putri Maulidya Sari; Budi Jatmiko; Nadi Suprapto (Jurnal Penelitian Pendidikan IPA, 2023)
PhysicsÂ is a science that can solve various problems that exist in everyday life in the form of technology. Therefore physics problem-solving skills are trained in school learning. This study aimed to determine the profile of students' physics problem-solving skills with physics case studies in everyday life. This study used a quantitative descriptive method and involved 55 students of senior high school in XII class who were randomly selected. The data used in this study were student response data to questionnaires and test results through problem-solving skills questions. Based on the questionnaire results, students felt they had problem-solving skills at the medium level of 38% and 62% high. Meanwhile, for test results using problem-solving skills questions, there was a decrease in level. As many as 7% of students have very high problem-solving skills, 18% high, 58% medium, and 17% low. The differences that arise show that there are problems in learning and the problem models given in physics learning at school.